2016
DOI: 10.1590/0103-8478cr20151447
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Alternaria isolates and reaction of potato genotypes to early blight

Abstract: Early blight is one of the most important fungal diseases of potato. The objective of this study was to evaluate the in vitro reaction of potato genotypes to the severity of early blight and compare the species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A . solani is considered to be an asexual pathogen, but some reports suggest parasexual reproduction is occurring in different populations and maybe even between related species (Alvarenga et al, 2016 ; Meng et al, 2015 ; Zhao et al, 2021 ). Therefore, we looked for signatures for recombination using LDHelmet (Chan et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A . solani is considered to be an asexual pathogen, but some reports suggest parasexual reproduction is occurring in different populations and maybe even between related species (Alvarenga et al, 2016 ; Meng et al, 2015 ; Zhao et al, 2021 ). Therefore, we looked for signatures for recombination using LDHelmet (Chan et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…One additional outcome of our study is clear evidence for recombination. Previous studies have suggested (para-)sexual recombination needs to happen in the field in order to explain the observed diversity patterns (Alvarenga et al, 2016;Meng et al, 2015;Zhao et al, 2021), but the use of markers with low resolution left this open for confirmation. We used whole-genome data and three different methods to test possible recombination.…”
Section: Adhakiri Et Al Compared Field Population Diversity Of Threementioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of vegetative compatibility, also referred to as mycelial compatibility, is a prerequisite for the parasexual cycle and therefore often interpreted as evidence or a hint for parasexual recombination. A. solani and A. grandis from potato both show vegetative compatibility (Alvarenga et al., 2016 ; van der Waals et al., 2004 ). Zhao, Fan, et al.…”
Section: Reproduction and Recombinationmentioning
confidence: 99%